Perlindungan Hukum terhadap Konsumen dalam Transaksi E-Commerce (Studi Kasus E-Commerce pada Media Sosial Instagram) - Muhammad Reza; Slamet Riyanto Anwar; Muhammad Fahruddin (Jurnal Hukum Jurisdictie, 2021)
The issue of consumer protection in e-commerce is an important aspect to pay attention to because some of the typical characteristics of e-commerce will put consumers in a weak or disadvantaged position. Therefore, this research and writing focuses on the formulation of the problem, namely: 1. How is legal protection for consumers in transacting through Instagram media? 2. What is the Consumer Protection Law No. 8 of 1999 can protect consumers in e-commerce transactions? 3. What are the forms of responsibility of business actors related to fulfilling consumer rights in buying and selling transactions on Instagram media? This study aims to determine the legal protection of consumers in transacting through Instagram media, analyzing the Consumer Protection Law No. 8 of 1999 which can protect consumers in e-commerce transactions and find out the forms of responsibility of online business actors related to fulfilling consumer rights in buying and selling transactions on Instagram media. This research uses normative legal methods and statutory approaches as well as case studies.